2004
DOI: 10.1002/pca.784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction method on the yield of furanocoumarins from fruits of Archangelica officinalis Hoffm.

Abstract: Optimal conditions for the extraction and analysis of furanocoumarins from fruits of Archangelica officinalis Hoffm. have been determined. The following extraction methods were used: exhaustive extraction in a Soxhlet apparatus, ultrasonication at 25 and 60 degrees C, microwave-assisted solvent extraction in open and closed systems, and accelerated solvent extraction (ASE). In most cases the yields of furanocoumarins were highest using the ASE method. The effects of extracting solvent, temperature and time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 22 publications
5
29
0
Order By: Relevance
“…lobata, and A. archangelica) were selected. The extracts were prepared in order to insure that they contain the metabolites that are ingested when the medicinal plant is orally taken: a methanolic extract of the fruits from A. archangelica mostly composed of furanocoumarins [43,44], a decoction of aerial parts of W. indica containing quinoline alkaloids [33], and a decoction of roots of P. montana var. lobata with flavonoid glycosides [35].…”
mentioning
confidence: 99%
“…lobata, and A. archangelica) were selected. The extracts were prepared in order to insure that they contain the metabolites that are ingested when the medicinal plant is orally taken: a methanolic extract of the fruits from A. archangelica mostly composed of furanocoumarins [43,44], a decoction of aerial parts of W. indica containing quinoline alkaloids [33], and a decoction of roots of P. montana var. lobata with flavonoid glycosides [35].…”
mentioning
confidence: 99%
“…Because of previous reports, that methanol was the best extractant for the furanocoumarins [10,22], this solvent (100% methanol and 80% aqueous solution of methanol) was used in our experiments. Results of the investigation (Table II) showed that extraction in Soxhlet apparatus was the most efficient for the isolation of isopimpinellin and umbelliferone, while ASE gave the highest yield of xanthotoxin, pimpinellin (100 °C, 100% methanol as extractant) and bergapten (80 °C, 80% aqueous solution of methanol as extractant).…”
Section: Resultsmentioning
confidence: 99%
“…Traditional liquid-solid extraction (LSE) procedures (e.g., Soxhlet extraction and percolation) are generally labor-intensive and time-and solvent-consuming methods. New liquid-solid extraction methods (LSE) such as microwave-assisted solvent extraction (MASE), accelerated solvent extraction (ASE), and ultrasoundassisted extraction (USAE) require shorter extraction time and the use of low amount of solvents, allow for simultaneous parallel processing of several samples, and are automatic but are more expensive due to special equipment devices [9,10]. The important step in sample preparation is the purification of crude extract usually by solid-phase extraction (SPE) or more rarely by liquid-liquid extraction (LLE).…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated the highest yield of psoralens by ASE, using methanol or petroleum ether as the extractant. It was also reported that microwave-assisted solvent extraction in the closed system probably causing the change of analytes (Waksmundzka-Hajnos et al, 2004a).…”
Section: Waksmundzka-hajnos Et Al (2004) Compared Methods Of Extractmentioning
confidence: 99%